Novel Tripodal Polyamine Tris-Pyrene: DNA/RNA Binding and Photodynamic Antiproliferative Activity - Marta Jurković; Marijana Radić Stojković; Ksenija Božinović; Davor Nestić; Dragomira Majhen; Estefanía Delgado-Pinar; Mario Inclán; Enrique García-España; Ivo Piantanida (MDPI AG, 2023)
A novel tri-pyrene polyamine (TAL3PYR) bearing net five positive charges at biorelevant conditions revealed strong intramolecular interactions in aqueous medium between pyrenes, characterised by pronounced excimer fluorescence. A novel compound revealed strong binding to ds-DNA and ds-RNA, along with pronounced thermal stabilisation of DNA/RNA and extensive changes in DNA/RNA structure, as evidenced by circular dichroism. New dye caused pronounced ds-DNA or ds-RNA condensation, which was attributed to a combination of electrostatic interactions between 5+ charge of dye and negatively charged polynucleotide backbone, accompanied by aromatic and hydrophobic interactions of pyrenes within polynucleotide grooves. New dye also showed intriguing antiproliferative activity, strongly enhanced upon photo-induced activation of pyrenes, and is thus a promising lead compound for theranostic applications on ds-RNA or ds-DNA targets, applicable as a new strategy in cancer and gene therapy.